Urban drainage planning in medium-sized cities of the Triângulo Mineiro and Alto Paranaíba (Sustainability in Debate, 2018)
The relations between the natural environment and the cities changed throughout the years mainly due to economic development and the functions assumed by urban space. These modifications brought manifold environmental problems that challenge urban planners not only from metropolises. Given their less dense occupation compared to larger cities, and since their laws concerning urban drainage are still being developed , medium-sized cities have larger possibilities to adapt their planning to this thematic. This paper discusses measures applied to urban drainage planning proposed in six medium cities in the Triângulo Mineiro and Alto Paranaíba regions. Citizens' disarticulated participation in the planning process, disparity in expenditures for different measures and excuses for the adoption of some measures, which were bolstered by problems that could have been prevented with previous urban drainage management were among the results.